Ausstellungs-Saison 1983/84 : Galerie Paul Maenz Köln. - Paul Maenz, Köln (Köln : Galerie Paul Maenz, 1984)
Kiefer, Anselm ; Fabro, Luciano ; Disler, Martin ; Haring, Keith ; Kapoor, Amish ; Woodrow, Bill ; Dahn, Walter
Duits
boek